Method for Extracting Viral Hemagglutination-Inhibiting Antibodies from the Nonspecific Inhibitors of Serum - Altemeier, William A. (1970)
Various methods are used to remove nonspecific inhibitors from sera before titering viral hemagglutination-inhibiting antibodies. These methods have several undesirable features; some are tedious and time-consuming, some remove antibody along with nonspecific inhibitors, and different techniques are usually required to remove the nonspecific inhibitors for different viruses. This communication describes a single method that uses diethylaminoethyl-Sephadex to extract the immunoglobulin G antibodies for several viruses from nonspecific inhibitors. The procedure is fast, simple to perform, and removed the nonspecific inhibitors for influenza, Western equine encephalitis, dengue-2, and rubella viruses.